Health-related quality of life and disability in adults with juvenile idiopathic arthritis - Oliveira Ramos, Filipa (2021)
Objective To compare physical disability, mental health, fatigue and health-related quality of life (HRQoL) across juvenile idiopathic arthritis (JIA) categories in adulthood and between JIA and adult-onset rheumatic diseases. Methods Cross-sectional analysis nested in a cohort of adult patients with JIA registered in the Rheumatic Diseases Portuguese Register (Reuma.pt). Physical disability (Health Assessment Questionnaire - Disability Index), mental health symptoms (Hospital Anxiety and Depression Scale), fatigue (Functional Assessment of Chronic Illness Therapy - Fatigue Scale (FACIT-F)) and HRQoL (EuroQol-5D (EQ5D) and Short Form (SF-36)) were compared across JIA categories. Patients with polyarticular JIA and enthesis-related arthritis (ERA) JIA were compared respectively to patients with rheumatoid arthritis (RA) and spondyloarthritis (SpA), matched for gender and age, adjusted for disease duration and activity. Results 585 adult patients with JIA were included. Comparison across JIA categories showed that persistent oligoarthritis and patients with ERA reported a higher score in EQ5D and SF-36 physical component when compared with other JIA categories. Polyarticular JIA reported less disability and fatigue than patients with RA (median Health Assessment Questionnaire of 0.25 vs 0.63; p<0.001 and median FACIT-F score 42 vs 40; p=0.041). Polyarticular JIA had also better scores on EQ5D and all domains of SF-36, than patients with RA. Patients with ERA reported less depression and anxiety symptoms (0% vs 14.8%; p=0.003% and 9% vs 21.3%; p=0.002) and less fatigue symptoms (45 vs 41; p=0.01) than patients with SpA. Conclusion Persistent oligoarticular JIA and ERA are the JIA categories in adulthood with better HRQoL. Overall, adult polyarticular and patients with ERA JIA have lower functional impairment and better quality-of-life than patients with RA and SpA.